How to Draft a Judicial Oath - Tammam Abdul Latif Al- Shishakli, (International Journal of Law Research and Studies, 2025)
One of the most important basic matters that the civil judge relies on in resolving the disputes that arise before him is the methods of judicial proof, which is the evidence that the parties present before the court to prove their rights. Since the right is devoid of his evidence in the event of a dispute becomes equal to nothingness, as it is impossible to enforce its respect by a court order on those who deny it. The oath is considered one of the most important evidences that prove the existence of these rights. I consider the oath to be one of the unusual methods of proof, and it is the evidence from which the meaning is derived on the fact that is required to be proven, thus making it proven even if it is not proven with certainty. It is one of the methods of proof that has an effect clear and productive in daily applications of disputes brought before the courts. There is no disagreement that the oath is one of the most important pieces of evidence stipulated by law. Indeed, it is the last resort to which litigants resort when they are unable to prove their case, given the religious and devotional meaning of the oath. Perhaps we would not be exaggerating if we said that the oath it was once the basic pillar of judicial proof, as testimony was the first piece of evidence and required the witness to take an oath. Thus, the oath was the basis of the testimony that the plaintiff relied on to prove his case, and at the same time, it was what the defendant relied on to deny the alleged fact. In any case, the oath is evidence. It is of a religious nature, based on a person's conscience and religion, and is a last resort resorted to by a litigant when they have no evidence to support their claim. For an oath to be considered legal evidence, it must be taken in a specific form before a court. This form must be consistent with the facts to be proven and must not lead to evasion of its consequences. Courts often encounter the problem of formulating the oath and the extent to which it applies to the facts required to be proven. The law requires that the facts required to be proven by the parties be precisely defined so that the evidence, including the oath, is applicable to them. If these facts are defined, the oath will be formulated in accordance with them, and the court may amend its wording if it is not applicable to the facts.Because of the importance of this topic and its frequent occurrence in daily life, lawsuits are often decided by oath, especially the decisive oath. Anyone who is unable to provide evidence to prove his claim is considered unable to prove it and has the right to have his opponent swear the decisive oath. Likewise, if the evidence of proof is incomplete or weak, the judge completes his conviction by directing the oath. The supplementary oath formula is formulated for each of these two types. The formula is formulated according to the facts, the parties' claims, and their defenses, as we mentioned earlier. Often, the formula is inconsistent with the facts. Therefore, we have researched this topic.
Keywords: Drafting the Judicial Oath; Civil Judge; Dispute Resolution